MedusoZoa – An Immersive and Interactive Virtual Reality Installation in a Museum - Souza, Alyson Matheus de Carvalho; Barbosa, Daniel M Do N; Bessa, Olavo F M; Ramos, Everardo A; Rennó-Costa, César (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2022)
Museums are plural spaces that can exhibit different forms of art, cultural pieces, as well as educational content. In this environment, virtual reality (VR) is being used as a tool to enhance those spaces and create new experiences that were not possible before. This paper describes the process of creating such an experience by reporting on the conceptual development, technical development, deployment, and evaluation of MedusoZoa, an immersive and interactive VR system that was installed in the Câmara Cascudo Museum as part of the museum week. The system used a black-painted dark room with four projectors to create an experience were virtual beings – jellyfishes in this case – appeared to be swimming around the room, following a simple schooling behavior based on a classic flocking algorithm and interacted, using a Kinect v2 sensor, with the participants that entered the room.